CHARACTERIZATION OF ELECTROMAGNETIC VIBRATION BASED ENERGY HARVESTING SYSTEM - Mohamed, Saratul Akma Bt (Universiti Teknologi PETRONAS, 2012)
This work presents the characterization of electromagnetic vibration based energy harvesting system. Energy harvesting is the process which energy is derived from external sources, captured, and stored for low power application devices. Vibration energy is an alternative energy sources beside solar, wind, and thermal energies. Energy harvesting is crucially important as it is environmental friendly and renewable sources. Overall, the electromagnetic vibration based energy harvesting converted vibration energy into electrical energy based on electromagnetic principle and second order mass spring system. It mainly consists of proof mass, vibrating membrane (spring), coil and also permanent magnet. The main objective of this project is to perform the characterization for electromagnetic vibration based energy harvester. The characterizations are divided to two parts which cover both the electrical and mechanical characterizations. Under the electrical characterization, the open loop, closed loop, impedance matching and the effect of difference gravitational acceleration to output voltage are investigated. For mechanical characterization, the resonance frequency, bandwidth frequency and damping ratio are analyzed. From the electrical and mechanical characterization, it was found that the open loop voltage produced by the device is 0.6759V, while the close loop voltage is 0.3073V at 260 matched impedance. Device resonance occurs at 22.7 Hz with damping ratio of 0.001862 and 10Hz operating bandwidth. From the characterization results, this device is found to be suitable for low power and autonomous applications such as the wireless sensor network, memory cell for portable electronic device and others.